The Interaction Between Epigenetic Changes, EMT, and Exosomes in Predicting Metastasis of Colorectal Cancers (CRC) - Yang, Meiqi; Sun, Mingjun; Zhang, Huijing (Frontiers in Oncology, 2022)
Colorectal cancers (CRCs) are among the most lethal malignant cancers worldwide. Metastasis is such a terrible event that it decreases overall survival in CRCs. Epigenetic change plays a vital role in the epithelial to mesenchymal transition (EMT) that is a crucial phenotype for metastasis, mainly including DNA methylation, non-coding RNAs (ncRNAs), and N6-methyladenosine (m6A) RNA are seemed to be valuable biomarkers in CRCs. For ncRNAs, there exists a "molecular sponge effect" between long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs). Exosomes detection is a novel method for CRCs, especially for predicting metastasis. There is a close relationship between exosomes and EMT in CRCs. This review emphasized DNA methylation, ncRNAs, and m6A RNA in plasma CTCs on predicting CRCs metastasis.